Entropy Coders of the H.264 /AVC Standard Algorithms and VLSI Architectures - Tian, Xiaohua; Le, Thinh M.; Lian, Yong. (2011)
This book presents a collection of algorithms and VLSI architectures of entropy (or statistical) codecs of recent video compression standards, with focus on the H.264/AVC standard. For any visual data compression scheme, there exists a combination of one, two, or all of the following three stages: spatial, temporal, and statistical compression. General readers are first introduced with the various algorithms of the statistical coders. The VLSI implementations are also reviewed and discussed. Readers with limited hardware design background are also introduced with a design methodology starting from performance-complexity analysis to software/ hardware co-simulation. A typical design of the Context-based Adaptive Binary Arithmetic Coding (CABAC) encoder is also presented in details. To support System-on-Chip design environment, the CABAC design is wrapped with a SoC-based Wishbone system bus interface.
Introduction to Video Compression -- Review of Arithmetic Coding and CABAC -- Review of Existing Statistical Codec Designs -- Design of a CABAC Encoder -- Efficient Architecture of Context Modeling of CABAC Encoder -- Design of System Bus Interface & Inter-connection of SoCbased CABAC Encoder.
Keywords: Engineering; COMMUNICATIONS ENGINEERING, NETWORKS; TELECOMUNICACIÓN